Pharmaceutical care in the management of people with type 2 diabetes mellitus: a randomized controlled trial / Chung Wen Wei - Chung, Wen Wei (2014)
Diabetes mellitus is a lifelong chronic condition that requires continuous healthcare and patient’s self-management. Lifestyle modifications and adherence to anti-diabetes medications are the major determinants of therapeutic success in the management of diabetes. The fundamental goal of pharmacy practice today is to provide PC which directly influences effective, rational and safe medication use, leading to better health outcomes. Studies which evaluated the effects of PC in the management of people with diabetes found a statistically significant reduction in HbA1C in the intervention group. However, most studies in the literature were conducted in developed countries. Therefore, the present study is warranted to investigate the effects of a pharmaceutical care (PC) model in the management of people with type 2 diabetes in Malaysia. A total of 241 people with type 2 diabetes were recruited from the Diabetes Clinic of the University Malaya Medical Centre (UMMC) and allocated at random to the control (n=121) or intervention (n=120) group. Participants in the intervention group received pharmaceutical care (PC) from an experienced pharmacist while those in the control group were provided the standard pharmacy service. A range of clinical outcomes that included fasting blood glucose (FBG), glyclated haemoglobin (HbA1C), lipid profile and blood pressure (BP); and non-clinical outcomes (medication adherence, knowledge of participants, quality of life and pharmaceutical care issues) were collected and analysed at baseline and then at 4, 8 and 12 months after the initiation of intervention. At baseline, there was no significant difference in demographic and clinical characteristics of the participants between the control and intervention groups. Significant reductions in mean (standard deviation, SD) of FBG [9.4 (3.4) mmol/L versus 7.5 (2.3) iv mmol/L, HbA1C [9.6 (1.3)% versus 8.2 (1.3)%], systolic BP [142.9 (18.4) mmHg versus 134.0 (15.1) mmHg], diastolic BP [79.5 (10.9) mmHg versus 77.0 (9.8) mmHg] were found between the control and intervention group 12 months after the provision of PC. In addition, medication adherence (p = 0.001) and knowledge of participants (p < 0.001) in the intervention group increased significantly. The control group on the other hand, showed no significant improvement in clinical outcomes. During the study period, the pharmacist identified 408 PC issues (PCIs) and facilitated 598 PC interventions. Of these 408 PCIs, the pharmacist in this study managed to solve 333 (81.6%). Each drug -elated problem (DRP) were linked to at least three root causes that were related and directed to the participants (45.7%) or their caregivers (54.8%). In conclusion, the provision of the PC model used in this study for the management of type 2 diabetes mellitus (T2DM) has produced positive effects on both clinical and behavioural outcomes of the intervention participants. Therefore, collaborative efforts between pharmacist and other healthcare professionals should be implemented in all healthcare institutions to achieve more effective, rational and safe medication use and hence, better clinical outcomes.